Analysis of the factors that initiate polymerization stress: a systematic review - Z. S. Khabadze; Yu. A. Generalova; M. G. Sheroziia; A. A. Nedashkovsky; V. S. Shubaeva (Эндодонтия Today, 2020)
Aim. To consider the problem of polymerization stress. Polymerization stress Is one of the main causes of loss of marginal Ш and subsequent postoperative manifestations, such as hypersensitivity, marginal staining, secondary carles, deformation of underlying tooth tissues.Materials and methods. A systematic review of the literature In the electronic databases Google Scholar and Pubmed was conducted. Articles related to the problem of polymerization stresses formation In dental composite materials, as well as factors that directly affect this process, are considered and Included.Resuits. 68 articles were analyzed during the review. After making the selection based on the exclusion criteria, the numberofincluded studies was 31.Conciusion. According to the studied publications, the development of shrinkage stresses Is In^uenced by four main groups of factors, the manifestations of which can be minimized as a result of modifying the structure of the composite material and methods of working with It.